Vertical accountability among ministries of state in an emerging economy: A case study of Ghana - Joseph Ofori Acheampong; Michael K. Dzordzormenyoh; Justice Nyigmah Bawole; Albert Ahenkan; Emmanuel Kojo Sakyi (Cogent Business & Management, 2023)
Since 1992, Ghana has implemented several initiatives and reforms such as the National Anti-Corruption Plan (NACAP), Right to Information (RTI) Act, Economic and Organized Crime Office (EOCO), and the Office of the Special Prosecutor (OSP) with the goal of improving accountability while reducing corruption. These policies provide researchers with a lot of opportunities to examine how effective these programs have been as well as their impact on accountability. Hence, the present study seeks to accomplish three main objectives: 1) to explore the factors that facilitate vertical accountability; 2) to explore the limitations to vertical accountability; and 3) to investigate the benefits of vertical accountability in Ghana. To accomplish these objectives, we interviewed twenty directors in seven ministries of state and ten experts across civil society and academia in Ghana. We found that the disclosure of financial income, assets, and interest, the Right to Information (RTI) Act; merit-based recruitment, proper record keeping, performance-based evaluation, training and development, the absence of corruption, and conflicts of interest are major drivers of vertical accountability in Ghana. Additionally, we found that the presence of corruption, nepotism/patron-clientelism, conflict of interest, a lack of political commitment and participation, inadequate resources, and weak complaint and accountability mechanisms limit vertical accountability. Finally, the benefits of vertical accountability include improvements in openness and fairness, effective and efficient utilization of scarce resources, integrity, and trust. These results were extensively discussed, while recommendations for future studies were proffered.
Keywords: 650; agency theory; corporate governance; Ministries of State; top-down; vertical accountability